La memoria de la ciudad en TAFOS: antropología visual cuando el otro tiene la cámara (portafolio fotográfico con breve prólogo) - Ramírez Corzo, Daniel (2007)
This paper offers and analyses a selection of pictures —with special emphasis on those representing urban scenes — from the photographic collection of Tafos’ Social Photography Workshop. Its main purpose is to highlight some important issues in contemporary discussion about anthropology in general and visual anthropology in particular: (1) theoretical and methodological issues and aspects associated with the experience developed by TAFOS in the field of visual anthropology, and (2) the role that these pictures may have in the construction of Lima’s collective memory.